Intra-cavity photodetachment microscopy and the electron affinity of germanium. (19th May 2015) - Bresteau, D; Babilotte, Ph; Drag, C; Blondel, C
Abstract: A beam of Ge − ions produced by a cesium sputtering ion source is photodetached, in the presence of an electric field, inside a linear optical cavity injected with a single mode ring Ti:Sa laser. The laser wavenumber can be set either above the highest fine-structure excitation threshold or just above the, intermediate fine-structure threshold of the ground-term of Ge I. A single-electron interferogram is produced, according to the principles of photodetachment microscopy, which contains both photoelectron energies produced by the two opposite wave vectors contained in the optical cavity. This makes the Doppler-free measurement of the photodetachment threshold even more direct than with the usual double-spot photodetachment microscopy method, at the expense of some reduction of the contrast in the interferograms. Both methods concur in producing a revised value of the electron affinity of germanium: or, one order of magnitude more precise and significantly smaller than the last measured value or . This new technique can be applied to weaker detachment thresholds or p-wave detachment.